Analisis keuntungan pedagang Kelelawar di Pasar Tradisional Beriman Kota Tomohon - C J Masengie; T. F.D Lumy; I D.R Lumenta (Universitas Sam Ratulangi, 2022)
BENEFITS ANALYSIS OF BAT TRADERS IN TOMOHON CITY TRADITIONAL FAITH MARKETS. This study aims to determine how much profit bat traders get at the Tomohon Traditional Faith Market. This research was conducted at the Tomohon City Faith Traditional Market in December 2020 – March 2021 with a total of 10 bat traders as respondents. This study uses the Total Sampling method using primary and secondary data. This study is to analyze the profits of bat traders and find out what factors affect the profits of bat traders by using profit analysis and panel data regression analysis. Based on the results of this study indicate that the profit of bat traders for 6 months from a total of 10 respondents is Rp.134.929.333 with an average profit per month of Rp.2.248.822 for each respondent while for the factors that influence the the advantages of bat traders in the Tomohon City Faith Traditional Market are the number of bats sold and the selling price of the bats.